Reforming High-Stakes Police Departments: How Federal Civil Rights Will Rebuild Constitutional Policing in America - Dukanovic, Ivana (2016)
Over the past two decades, the Justice Department has untaken dozens of topdown interventions of local police departments plagued with unconstitutional policing. From Albuquerque, New Mexico, to Ferguson, Missouri, the Justice Department's Civil Rights Division has instituted reform in departments exhibiting patterns or practices that violate individuals' constitutional rights. The government's tool for imposing such reform and oversight on local, state power is a twenty-three-year-old statute: 42 U.S.C. 14141. This Note proposes that § 14141 is the change agent for rebuilding constitutional policing in America. But with change comes challenge, and many pushback departments continue to resist reform. The Note addressees these issue organizations, profiling the types of departments that welcome change and those that will push back on federal power. In addition, instances of backsliding in previously reformed police departments raise the question of whether § 14141 reform is sustainable. This Note proposes that sustainability of § 14141 reform can be advanced and maintained through the implementation of backup plans and internal monitoring. Applying these proposals to the most recent federal intervention, this Note uses the Ferguson Police Department as a case study and provides sustainability suggestions and predictions for the smallest department to ever undergo § 14141 reform. Lastly, this Note presents constitutional objections to strong use of § 14141